New pulse profile variability associated with a glitch of PSR J0738-4042. Issue 1 (21st November 2022) - Zhou, S Q; Gügercinoğlu, E; Yuan, J P; Ge, M Y; Yu, C; Zhang, C M; Zhang, J; Feng, Z W; Ye, C Q
ABSTRACT: The close correlation observed between emission state and spin-down rate change of pulsars has many implications both for the magnetospheric physics and the neutron star interior. The middle-aged pulsar PSR J0738-4042, which had been observed to display variations in the pulse profile associated with its spin-down rate change due to external effects, is a remarkable example. In this study, based on the 12.5 yr combined public timing data from UTMOST and Parkes, we have detected a new emission-rotation correlation in PSR J0738-4042 concurrent with a glitch. A glitch that occurred at MJD 57359 (5) (2015 December 3) with Δν/ν ∼ 0.36(4) × 10 −9 is the first glitch event observed in this pulsar, and is probably the underlying cause of the emission-rotation correlation. Unlike the usual post-glitch behaviours, the braking torque on the pulsar has continued to increase over 1380 d, corresponding to a significant decrease in $\ddot{ν }$ . As for changes in the pulse profile after the glitch, the relative amplitude of the leading component weakens drastically, while the middle component becomes stronger. A combined model of crustquake induced platelet movement and vortex creep response is invoked to account for this rare correlation. In this scenario, magnetospheric state-change is naturally linked to the pulsar-intrinsic processes that give rise to a glitch.